Envelope design for thermal performance in residential buildings under hot arid climate conditions - Latreche, Sihem; Sriti, Leila; Mansouri, Khaled; Berbouche, Chafia (Technium Social Sciences Journal, 2022)
In a typical hot arid climate, heat gains throughout the building envelope are responsible for more than 70% of the total thermal load. Furthermore, the thermal behavior of a building depends on the formal and constructive choices implemented in the envelope design. Since the envelope is exposed to outdoor conditions, it is crucial to give a major interest to the thermal characteristics of its structural components (i.e., walls, roof and windows). These elements are in charge of thermal exchanges between the building and its environment that occurs by heat transmission, thermal heat storage, solar heat gain and air infiltration. In return, implementing proper climatic responsive design strategies could potentially improve the envelope thermal performance while significantly reducing the building’s energy needs. The present study addresses the thermal behavior of the envelope under hot arid climate conditions by focusing on residential buildings. The research was conductuted in the city of Biskra (Algeria); it deals with the thermal investigation of the urban individual self-produced houses as the most widespread housing type in Ageria. The study explores the potential of improving the climatic adaptability of the envelope while respecting the specific characteristics of this self-produced dwelling. To achieve this goal, optimization scenarios of the building envelope were examined by implementing a set of selected passive design strategies. The process of optimisation was initiated by performing a simulation using TRNSYS 17 software, followed by a sensitivity analysis of the envelope design elements relating to their material characteristics (architectural and constructive to evaluate their effect in regulating indoor air temperatures and providing comfort condition. The results demonstrate significant improvements in the thermal responsive of the envelope and a consequent decrease in indoor temperatures. Moreover, the study defines the most prominent strategies in the process of optimization of the envelope. Accordingly, using suitable constructive systems and materials for walls and roofs in addition to adequate orientation and judicious ratios of openings, while implementing insulation and exterior light colors found to be the most efficient design strategies.